2001
DOI: 10.1002/ar.10015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of venom expulsion in Crotalus, with special reference to the role of the fang sheath

Abstract: A combination of anatomical and experimental preparations were used to explore the function of the venom delivery system in rattlesnakes (Crotalus). The distal end of the venom duct is compressed near the point where it empties into the venom chamber, a space surrounding the fang defined by the fang sheath. Within the venom chamber, the inner fang membrane lies obliquely over the base of the fang at least partially occluding the entrance orifice. When the fang is retracted the combination of the compressed ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
25
1
2
Order By: Relevance
“…The similarity between our findings and the earlier experimental study of the viperid Crotalus (principally Young et al, 2000Young et al, , 2001a suggests functional convergence between these two lineages.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The similarity between our findings and the earlier experimental study of the viperid Crotalus (principally Young et al, 2000Young et al, , 2001a suggests functional convergence between these two lineages.…”
supporting
confidence: 88%
“…Recent experimental work has demonstrated that displacement of the fang sheath towards the base of the fang, as well as pressure changes in the venom delivery system, can significantly influence venom flow (Young et al, 2001a(Young et al, , 2003. In most venomous snakes physical displacement of the fang sheath, either by a container during milking or by the target surface during fang penetration, is a prerequisite for venom release.…”
mentioning
confidence: 99%
“…Young et al (2000) supported Rosenberg's model by demonstrating a relationship between the contractile state of the extrinsic venom gland musculature and venom pressure in Crotalus atrox. Additional experimental analyses of crotalids demonstrated that the soft tissues of the fang sheath play a functional role in venom delivery (Young et al 2001a). This led to the formulation of a new model, the pressure-balance model, for venom injection in snakes.…”
Section: Introductionmentioning
confidence: 99%
“…(CAMPBELL;LAMAR, 1989 Uma das principais características da família Viperidae é a presença de um aparelho inoculador de veneno altamente especializado e eficiente para a captura de presas. A dentição dessas serpentes é do tipo solenoglifodonte, isto é, possuem um par de dentes maxilares modificados para a injeção de veneno e está associado a um mecanismo complexo que permite uma grande abertura bucal, facilitando assim o posicionamento do dente em relação à presa (Figura 3) (GOMES; PUORTO, 1993 Quando a serpente está de boca fechada as presas ficam deitadas na horizontal no interior de um tecido conjuntivo denso irregular, denominado de bainha protetora que forma ligações fracas ao longo da superfície da presa em cerca de um terço do comprimento da presa (YOUNG et al, 2001 , 1971;ZAGO, 1971;SCHAEFFER JR et al, 1972a,b;ORON;BDOLAH, 1973;KOCHVA, 1978;BDOLAH, 1979;CARNEIRO et al, 1991;MACKESSY, 1991;SALOMÃO, 1991 A dessensibilização prolongada dos adrenoceptores  e  possibilitou a descoberta, in vivo, da importância da estimulação desses adrenoceptores para o desencadeamento do ciclo de veneno (YAMANOUYE et al, 2000;KERCHOVE et al, 2004;ZABLITH, 2007). Estudos sobre a sinalização após a estimulação dos adrenoceptores levaram a conclusão de que a noradrenalina é a responsável pela ativação da glândula de veneno (KERCHOVE et al, 2008;LUNA et al, 2009 1965;MACKESSY, 1991;SALOMÃO, 1991).…”
Section: Bothrops Jararacaunclassified
“…O sistema de entrega de veneno em serpentes Viperidae é regulado pela contração do músculo compressor de glândula que cobre a glândula principal de veneno e por mudanças de posicionamento da bainha da presa (YOUNG et al, 2001;KARDONG, 2007). Portanto, a expulsão do veneno é orquestrada por forças mecânicas.…”
Section: Glândula Acessóriaunclassified